2021
DOI: 10.5371/hp.2021.33.3.109
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Direct Anterior Approach for Revision Total Hip Arthroplasty: A Systematic Review

Abstract: The direct anterior approach (DAA) is an established approach for total hip arthroplasty (THA) but has been sparingly tried for revisions. The purpose of this study was to examine the available literature in order to consolidate information available on revision THA using the DAA. A PubMed, Embase, and Scopus search was performed using relevant keywords. Studies reporting on patients undergoing revision THA using DAA were included for analysis. In a review of the literature, nine studies matched the pre-decide… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 49 publications
1
0
0
Order By: Relevance
“…While several other systematic reviews and meta-analyses have analyzed surgical approaches in THA, the present review is the first to specifically investigate whether surgical approach in THA using dual mobility constructs affect clinical outcomes in patients undergoing primary THA. As in our current study, previous reviews have found that postoperative complications and dislocation rates are generally low following THA in non-high-risk populations, and that utilizing the DAA, ALA, DLA, or PLA may result in similar long-term outcomes [ 6 , 94 97 ]. For example, a 2017 systematic review of 42 studies found that functional hip outcomes (e.g., HHS) were significantly improved for DAA in the short-term (6 weeks postoperatively), but differences were not generally sustained past that point [ 6 ].…”
Section: Discussionsupporting
confidence: 67%
“…While several other systematic reviews and meta-analyses have analyzed surgical approaches in THA, the present review is the first to specifically investigate whether surgical approach in THA using dual mobility constructs affect clinical outcomes in patients undergoing primary THA. As in our current study, previous reviews have found that postoperative complications and dislocation rates are generally low following THA in non-high-risk populations, and that utilizing the DAA, ALA, DLA, or PLA may result in similar long-term outcomes [ 6 , 94 97 ]. For example, a 2017 systematic review of 42 studies found that functional hip outcomes (e.g., HHS) were significantly improved for DAA in the short-term (6 weeks postoperatively), but differences were not generally sustained past that point [ 6 ].…”
Section: Discussionsupporting
confidence: 67%
“…Multiple studies have reported that DAA for can be successfully used for rTHA. A systematic review by Singh et al reported on 319 rTHAs performed via the DAA across 9 studies, with 158 hips undergoing rTHA for aseptic loosening of the acetabular cup (Singh, Khurana, and Gupta 2021). They found that across the studies, most patients had a good or excellent outcome after rTHA and the overall complication rate was 1.6% (Singh, Khurana, and Gupta 2021).…”
Section: Discussionmentioning
confidence: 99%
“…A systematic review by Singh et al reported on 319 rTHAs performed via the DAA across 9 studies, with 158 hips undergoing rTHA for aseptic loosening of the acetabular cup (Singh, Khurana, and Gupta 2021). They found that across the studies, most patients had a good or excellent outcome after rTHA and the overall complication rate was 1.6% (Singh, Khurana, and Gupta 2021). Kurkis et al reported on 99 successful DAA rTHAs and showed that the DAA rTHA was associated with a lower risk of dislocations, but a higher risk of superficial wound complications (Kurkis et al 2021).…”
Section: Discussionmentioning
confidence: 99%